Colours and Shapes - Sirett, Dawn; Harvey, Victoria; King, Dave (London Dorling Kindersley Limited, 2009)
"From silky butterflies to bumpy oranges, there are all sorts of textures for baby to explore in this safe, sturdy book that encourages early learning"--Back cover
Picture Books
1 2 9 13 23
Keywords: Picture Books for children